2020
DOI: 10.1038/s41416-020-0827-5
|View full text |Cite
|
Sign up to set email alerts
|

Stearoyl-CoA-desaturase-1 regulates gastric cancer stem-like properties and promotes tumour metastasis via Hippo/YAP pathway

Abstract: Background Stearoyl-CoA desaturase-1 (SCD1) is reported to play essential roles in cancer stemness among several cancers. Our previous research revealed significant overexpression of SCD1 in primary gastric cancer stem cells (GCSCs), with its functional role still unknown. Methods We stably established three primary GCSCs by sphere-forming assays and flow cytometry. Protein quantification and bioinformatics analysis were performed to reveal the dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 34 publications
0
29
0
Order By: Relevance
“…Adherent cells were cultured in Dulbecco’s modified Eagle’s medium (DMEM, GIBCO, NY, USA) with 10% fetal bovine serum (FBS) and 1% P/S in a standard condition at 37 °C with 5% CO 2 . Gastric cancer stem cells (GCSCs) were obtained and cultured as previously described [ 13 , 14 ]. Briefly, GCSCs were extracted from fresh GC tissues resected in Chinese PLA General Hospital (PLAGH) and cultured in ultra-low-attachment 6-well plates (Corning, NY, USA) with modified DMEM/F12, 2% B27 supplements (Invitrogen, CA, USA), 1% ITS (insulin–transferrin–selenous acid, Corning, NY, USA), 20 ng/ml epidermal growth factor (Peprotech, Hartford, CT, USA), 10 ng/ml basic fibroblast growth factor (Peprotech), 10 ng/ml LIF (Peprotech) and 10 ng/ml gastrin I (Peprotech).…”
Section: Methodsmentioning
confidence: 99%
“…Adherent cells were cultured in Dulbecco’s modified Eagle’s medium (DMEM, GIBCO, NY, USA) with 10% fetal bovine serum (FBS) and 1% P/S in a standard condition at 37 °C with 5% CO 2 . Gastric cancer stem cells (GCSCs) were obtained and cultured as previously described [ 13 , 14 ]. Briefly, GCSCs were extracted from fresh GC tissues resected in Chinese PLA General Hospital (PLAGH) and cultured in ultra-low-attachment 6-well plates (Corning, NY, USA) with modified DMEM/F12, 2% B27 supplements (Invitrogen, CA, USA), 1% ITS (insulin–transferrin–selenous acid, Corning, NY, USA), 20 ng/ml epidermal growth factor (Peprotech, Hartford, CT, USA), 10 ng/ml basic fibroblast growth factor (Peprotech), 10 ng/ml LIF (Peprotech) and 10 ng/ml gastrin I (Peprotech).…”
Section: Methodsmentioning
confidence: 99%
“…It has been observed that the expression of SCD1 is upregulated in hepatocellular, renal clear cell, lung, prostate and breast cancer, which is associated with poorer prognosis (Fritz et al, 2010;Holder et al, 2013;von Roemeling et al, 2013;Huang et al, 2015;Wohlhieter et al, 2020). Recent evidence also supported that SCD1 involved in many tumor-related pathways and played important roles in the self-renewal, metastasis, and resistance to therapy in glioblastoma, breast, lung and bladder CSCs (Noto et al, 2013;Colacino et al, 2016;Li J. et al, 2017;Mukherjee et al, 2017;Noto et al, 2017;Pisanu et al, 2018;Pinkham et al, 2019;Gao et al, 2020;Yu et al, 2021).…”
Section: Lipid Desaturationmentioning
confidence: 99%
“…The inhibition of SCD1 led to the selective elimination of colon CSCs through suppressing Wnt and Notch signaling ( Yu et al, 2021 ). The results showed that the crosstalk between SCD1 and Hippo pathway played an important role in maintaining the stemness features of the lung, gastric, and melanoma CSCs ( Noto et al, 2017 ; Pisanu et al, 2018 ; Gao et al, 2020 ). Besides, the Notch signaling pathway mediated the homeostasis of liver cancer cells by controlling FAO by mediating the expression of the FAO-associated genes ( Song et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…In gastric cancer, SCD1 has found to be upregulated and this results in poor survival rates. Furthermore, this enzyme is able to induce tumorigenesis, drug resistance and metastasis by regulating GCSCs proliferation through the Hippo pathway ( 79 ). Hence CSCs, compared to their differentiated tumor counterparts, show an enhancement of lipid synthesis de novo , which is also reflected in the accumulation of intracellular lipids.…”
Section: Metabolic Profile Of Gastric Cancer Stem Cells (Gcscs)mentioning
confidence: 99%